Seven Profiles of Exemplary Religious Teachers: A Comparative Study in Southeast Asian Muslim Minority Countries - Susan San Htay; Ei Thet Hmoo Po; Krim Ulwi; Patri Patri; Julio Tomas Pinto (Khalifa Journal of Islamic Education, 2025)
Teachers are educators who devote themselves to an educational institution and have the task of guiding and teaching students both within and outside the curriculum. A teacher's character will have an impact on their students. Good character will have a positive impact, and conversely, bad character will have a negative impact. Therefore, teachers must have good character so that they can be role models for their students. This study aims to identify the characteristics of teachers so that they can be good role models for students and other teachers. This study uses a qualitative method with a phenomenological approach. The data sources were taken from observations and individual interviews with nineteen informants consisting of teachers and students using purposive sampling techniques. All data obtained were analyzed using the Miles and Huberman analysis technique. The results of the study show seven findings related to role model teachers in Islamic education in 2024. The seven findings are: i) able to instill Islamic values in students, ii) professional, iii) empathetic, iv) disciplined, v) responsible, vi) motivational, and vii) communicative. All of these findings are expected to serve as guidelines for teachers and as a primary reference for future researchers working on similar topics in different contexts.